2014
DOI: 10.1136/annrheumdis-2013-205171
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with damage accrual in patients with systemic lupus erythematosus: results from the Systemic Lupus International Collaborating Clinics (SLICC) Inception Cohort

Abstract: Background and aimsWe studied damage accrual and factors determining development and progression of damage in an international cohort of systemic lupus erythematosus (SLE) patients.MethodsThe Systemic Lupus International Collaborating Clinics (SLICC) Inception Cohort recruited patients within 15 months of developing four or more 1997 American College of Rheumatology (ACR) criteria for SLE; the SLICC/ACR damage index (SDI) was measured annually. We assessed relative rates of transition using maximum likelihood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
387
7
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 454 publications
(458 citation statements)
references
References 19 publications
33
387
7
11
Order By: Relevance
“…Concerning the comment of Bachmeyer, et al 1 on the low level of antimalarial usage (80%) in our cohort, we state that similar levels have been reported in other large registries such as the RELESSER group with 83% in 4024 patients 7 , while lower numbers were described in inception cohorts, such as the Systemic Lupus International Collaborating Clinics cohort, with 67% in 1722 patients 8 . Ocular and gastrointestinal toxicity along with intolerance in a certain number of patients may account for this.…”
Section: To the Editormentioning
confidence: 77%
“…Concerning the comment of Bachmeyer, et al 1 on the low level of antimalarial usage (80%) in our cohort, we state that similar levels have been reported in other large registries such as the RELESSER group with 83% in 4024 patients 7 , while lower numbers were described in inception cohorts, such as the Systemic Lupus International Collaborating Clinics cohort, with 67% in 1722 patients 8 . Ocular and gastrointestinal toxicity along with intolerance in a certain number of patients may account for this.…”
Section: To the Editormentioning
confidence: 77%
“…Many studies have shown that it is not, at any single occasion, raised disease activity that associates with poor prognosis and mortality, 10 but rather the acquired organ damage which is a product of medication side effects, comorbidities and disease activity over time. Apart from increased mortality, organ damage also implies a reduced physical function, quality of life and productivity for the patient [17]. Biomarkers with the potential to early identify individuals who are at risk of developing severe disease with subsequent organ damage are thus highly warranted.…”
Section: Resultsmentioning
confidence: 99%
“…The disease course in SLE is unpredictable with episodes of flares and remissions, sometimes leading to permanent organ damage and to preterm mortality [17,131]. Many studies have shown that it is not, at any single occasion, raised disease activity that associates with poor prognosis and mortality, but rather the acquired organ damage which is a product of medication side effects, comorbidities and disease activity over time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations